Assessment of the Effect of Seed Infection with Ascochyta pisi on Pea in Western Canada - Sivachandra Kumar, Nimllash T.; Banniza, Sabine (Frontiers in Plant Science, 2017)
The role of seed infection with Ascochyta pisi using naturally infected seeds with an incidence from 0.5 to 14.5% was studied in field pea experiments in western Canada at locations with historically low inoculum pressure. A significant effect of A. pisi seed infection on the emergence of seedlings was observed in one experiment and when all data were pooled, but emergence was only reduced minimally, and symptoms of A. pisi on the aerial parts of the seedlings were rarely observed. The level of seed infection at planting had no impact on A. pisi disease severity on mature plants, on seed yield and size, or on the incidence of A. pisi infection of harvested seeds although A. pisi was the dominant species recovered from seeds. Results suggest that the disease did not progress significantly from seeds to seedlings, hence did not contribute to infection of aerial parts of the plants, and therefore infected seeds cannot be regarded as a source of inoculum in the epidemiology of this pathogen under western Canadian growing coniditions. Assessing seed components of seeds with varying levels of A. pisi infection and seed staining revealed that the pathogen was present in all components of the seed, regardless of the severity of seed staining. This indicates that infected seeds may be an important way for the pathogen to survive in nature.